Costunolide ameliorates autoimmune uveitis by targeting USP15 to suppress TNF-α-induced retinal endothelial inflammation - Yu Gao; Xingran Li; Lingyu Dai; Xiang Luo; Guannan Su; Kai Shi; Ling Chen; Peizeng Yang (Proceedings of the National Academy of Sciences, 2026)
Autoimmune uveitis is a sight-threatening inflammatory disease, with the majority of entities driven by leukocyte infiltration into the retina. A critical early step in this process is the activation of retinal vascular endothelial cells (ECs), which up-regulate adhesion molecules that mediate T cell adhesion and subsequent extravasation. Here, we identify the small terpenoid compound costunolide (COS) as a potent suppressor of retinal endothelial inflammation and disease progression in experimental autoimmune uveitis (EAU). Quantitative proteomics of primary human retinal endothelial cells stimulated with TNF-α defined a proinflammatory endothelial signature and revealed induction of adhesion molecules. Screening of a focused library of 337 terpenoids uncovered COS as a top hit that markedly attenuated TNF-α-induced endothelial activation. In vivo, COS treatment significantly reduced clinical and histopathologic EAU scores, accompanied with reduced endothelial adhesion molecule expression and decreased T cell infiltration. Mechanistically, COS directly targeted deubiquitinase USP15, inhibiting USP15-dependent deubiquitination of TRAF1 and TNF signaling in retinal ECs. These findings establish COS as a candidate therapeutic agent for autoimmune uveitis and reveal a TNF-α–USP15–TRAF1 axis in retinal endothelium that can be pharmacologically exploited to limit pathogenic leukocyte trafficking.